Primer registro del pulpo de profundidad Muusoctopus longibrachus (Cephalopoda: Octopoda) para el mar peruano - Cardoso, Franz (2014)
The octopus deep-sea Muusoctopus longibrachus (Ibañez et al. 2006) is recorded for the first time in the Peruvian sea. Two male specimens were caught at 852 – 875 m depth between 05°08'S and 09°18'S. This species was known only from Chile, in the present study extends its distribution north to Peru.